A cold front induced co-occurrence of O3 and PM2.5 pollution in a Pearl River Delta city: Temporal variation, vertical structure, and mechanism. (1st August 2022) - He, Yuanping; Li, Lei; Wang, Haolin; Xu, Xinqi; Li, Yuman; Fan, Shaojia
Abstract: In this study, the spatiotemporal variabilities and characteristics of ozone (O3 ) and fine particulate matter (PM2.5 ) were reconstructed, and the interaction between meteorological conditions and the co-occurrence of O3 and PM2.5 in Zhuhai, a city in the Pearl River Delta (China), was analysed. The vertical distributions of lower tropospheric O3, aerosol extinction coefficient, and wind velocity were measured using a ground-based LiDAR system. The diurnal variations in air pollutant concentrations and meteorological conditions at ground level were examined from 28 November to December 8, 2020 considering the weather conditions in Zhuhai. Heavy pollution episodes with increased concentrations of O3 and PM2.5 were observed from 6 to 7 December after a period of cold air invasion. The maximum hourly average concentrations of O3 and PM2.5 at the ground level reached up to 190 μg/m 3, 98 μg/m 3, respectively. The horizontal wind speed rapidly decreased to less than 2 m/s during the heavy pollution episodes driven by O3 and PM2.5, whereas the vertical wind velocity was dominated by the downdraught. When the large-scale synoptic winds were weak, a strengthening sea breeze in the afternoon could promote the landward propagation of warm marine air masses, and a lower surface wind speed was driven by the convergence of cold air from the north and warm air from the south. In turn, this increased the residence time of air pollutants and promoted their conversion to secondary pollutants. Regarding the pollution sources, the results indicated that the Pearl River Estuary represented a 'pool' of O3 and PM2.5 pollution. In addition, the contribution of regional pollutant transport could not be ignored when considering the accumulative increase in air pollution. Overall, the relatively weak synoptic winds, low mixing height, and high generation of pollution around Zhuhai collectively resulted in high concentrations of O3 and PM2.5 . Graphical abstract: Image 1 Highlights: Complex air pollution episodes were observed after a period of cold air invasion. A LiDAR system was used for vertical observations of O3, aerosol, and wind. The heavy pollution episodes in Zhuhai occurred under the weak synoptic wind.